Overcoming Chemical and Mechanical Instabilities in Lithium Metal Anodes with Sustainable and Eco-Friendly Artificial SEI Layer - Song, Hyunsub; Lee, Jiyoung; Sagong, Mingyu; Jeon, Jiwon; Han, Yeji; Kim, Jinwuk; Jung, Hun-Gi; Yu, Ji-Sang; Lee, Jinwoo; Kim, Il-Doo (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2024)
Construction of a robust artificial solid-electrolyte interphase (SEI) layer has proposed an effective strategy to overcome the instability of the lithium (Li). However, existing artificial SEI layers inadequately controlled ion distribution, leading to dendritic growth and penetration. Furthermore, the environmental impact of the manufacturing process and materials of the artificial layer is often overlooked. In this work, a chemically and physically reinforced membrane (C-Li@P) composed of the biocompatible Li+ coordinated carboxymethyl guar gum (CMGG) and polyacrylamide (PAM) polymers serves as an artificial SEI membrane for dendrite-free Li. This membrane with hollow channels not only directs ion flux along the interspace of fibers, fostering uniform Li plating but also induces a desirable interface chemistry. Consequently, artificial SEI membrane-covered Li exhibits stable electrochemical plating/stripping reactions, surpassing the cycle life of approximate to 750% of bare Li. It demonstrates exceptional capacity retention of approximate to 93.9%, approximate to 88.1%, and approximate to 79.18% in full cells paired with LiNi0.8Mn0.1Co0.1O2 (NMC811), LiNi0.6Mn0.2Co0.2O2 (NMC622) and S cathodes, respectively over 200 cycles at 1 C rate. Additionally, the water-based green manufacturing and biodegradability of the membrane demonstrated the sustainable development and disposal of electrodes. This work provides a comprehensive framework for the design of an artificial layer chemically and physically regulating dendritic growth. Physical and chemical regulation leads to stabilization of lithium anode and solid-electrolyte interphase (SEI) layer with eco-friendly process from synthesis to disposal. image